Investigation of exchange coupling and microwave properties of hard/soft (SrNi0.02Zr0.01Fe11.96O19)/(CoFe2O4)x nanocomposites. (June 2022) - Almessiere, M.A.; Algarou, N.A.; Slimani, Y.; Sadaqat, A.; Baykal, A.; Manikandan, A.; Trukhanov, S.V.; Trukhanov, A.V.; Ercan, I.
Abstract: This article deals with the synthesis and the investigation of the structural features, magnetic and microwave properties of hard/soft (H/S) SrNi0.02 Zr0.01 Fe11.96 O19 (SrNiZr)/CoFe2 O4 (CFO) x ( x  = 1.0, 1.5, 2.0, 2.5, 3.0) nanocomposites (NCs). Products were manufactured via one-pot sol-gel auto-combustion approach. The formation of hard/soft phases was verified via X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM),  and high resolution transmission electron microscopy (HR-TEM) techniques. XRD analyses proved the presence of both hexagonal and cubic crystal structure in each H/S NCs. Vibrating sample magnetometer was employed to examine the magnetic features of the prepared NCs at room (RT; T = 300 K) and low temperatures (LT; T = 10 K). The magnetization (M) vs. applied field (H) curves displayed complete and good exchange coupling among the hard and soft phases for the different samples at 300 K. In contrast, an incomplete and weak exchange-coupled interaction was observed for all NCs at 10 K, excepting the SrNiZr/(CFO)1.0  NCs . The different magnetic parameters ( H c, M s, M r, and n B ) were extracted for the H/S SrNiZr/(CFO)x (x = 1.0, 1.5, 2.0, 2.5, 3.0) NCs at both temperatures. All products exhibited a single magnetic domain since the value of squareness ratio is M r /M s > 0.5. The correlation of the electromagnetic properties (frequency dependences of the permittivity/permeability and reflection losses) as function of the magnetic phase ratio in H/S SrNiZr/(CFO)x ( x  = 1.0, 1.5, 2.0, 2.5, 3.0) functional NCs were analyzed from S11–S21 parameters (2–18 GHz). It was observed strong correlation between the CFO content ( x ) and electrodynamic parameters (permittivity, permeability, and reflection losses). It is established that these materials can be applied for electromagnetic compatibility and radar-technologies.